Tobacco Cultivation in Latin America (2014)
This paper evaluates the importance of tobacco cultivation in Latin America. To this end the main variables of the sector will be analyzed, such as the quantity and value of production, the number of cultivated hectares and crop yields. The value of the sector as export strength is also studied. In addition, a comparison of direct employment generated by tobacco cultivation in tobacco countries of Latin America is created based on different sources. The results show that the production of Latin-American countries as a whole has been increasing in recent years, making the share of production of this continent close to 16% of world production. Argentina and Brazil stand out for their production to be placed among the ten largest producers in the world. The extension of cultivated area in the region reaches 13.55% of the area dedicated to tobacco in the world. The increase in production has driven a growth in the productivity of the product with a growing trend for the past several lustrums. This positive trend has been accompanied by an increase in prices paid to the grower, particularly since 2007. It is then a sector with a significant impact on the region. Tobacco cultivation has the capacity of generating 650,000 direct jobs and exporting U.S. $ 3,788 million annually. Considering the analysis only involves direct employment, these figures are very significant.